Skład ciała seniorek z uwzględnieniem zjawiska sarkopenii = Body composition of older women in consideration of sarcopenia - Nowacka-Chiari, Ewa; Skorupka, Ewa (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article was to present body composition of older women (students at the Universities of the Third Age in the Lubuskie Voivodeship) and its assessment in consi-deration of selected indicators of sarcopenia. The study involved 111 women between the ages of 58 and 84. Their body composition was assessed by using Bioelectrical Impedance Analysis (BIA). Symptoms of sarcopenia were determined on the basis of muscle mass (SMI [%], MMI [kg/m2], FFMI [kg/m2]), both hands grip strength, and the walking speed [m/s]. The differences noted in parametric and nonparametric features were at the level of p<0.05. Similar proportions of body components were observed in younger and older senior women, including clear excess of fat mass.
Keywords: seniorzy; skład ciała; wskaźniki sarkopenii; seniors; body composition; indicators of sarcopenia